The - Scheinrock, Jeff (John Wiley & Sons, Inc., 2013)
The tools of a digital age make it easier than ever to start a new business. And with billion-dollar IPOs and acquisitions making weekly headlines, the potential rewards are enormous. But even with all of the advantages and resources that today's entrepreneurs have access to, the likelihood of any one business succeeding is slim. That's why you need the simple, clear lessons found in The Agile Startup. Engaging and informative, The Agile Startup doesn't offer step-by-step instructions on how to build a better mousetrap. Instead, it shows you how to build companies that continually adapt to the "real" world. Along the way, you'll discover you're not alone in your entrepreneurial endeavors, and that almost every challenge a startup can face has already been faced, and overcome, by someone in the past